PENGARUH BEBAN KERJA DAN KOMITMEN ORGANISASI TERHADAP KINERJA PEGAWAI MELALUI KEPUASAN KERJA PADA DINAS PENDAPATAN KOTA KENDARI - Laode Rahmat Malbar; Endro Sukotjo; Yusuf Yusuf; Sri Wiyati Mahrani (Jurnal Manajemen, Bisnis dan Organisasi (JUMBO), 2022)
The purpose of this study was to determine and analyze workload, organizational commitment to employee performance through job satisfaction at the Kendari City Revenue Service. This research approach is a survey with an explanatory research design. Data collection is done by using an instrument in the form of a questionnaire. The population of this study were all employees of the Kendari City Revenue Service as many as 104 people. The determination of the number of samples was carried out using a census. The analytical tool used is SEM with the AMOS program package.The results showed that (1) Workload had a negative and insignificant effect on employee job satisfaction at the Kendari City Revenue Service. (2) Organizational commitment has a positive and significant effect on employee job satisfaction at the Kendari City Revenue Service. (3) Workload has a negative and insignificant effect on employee performance at the Kendari City Revenue Service. Organizational commitment has a positive and significant effect on employee performance at the Kendari City Revenue Service Office. (4) Job satisfaction has a positive and significant effect on employee performance at the Kendari City Revenue Service. (5) Job satisfaction is not able to mediate the effect of workload on employee performance at the Kendari City Revenue Service. (6) Job satisfaction is able to mediate the effect of organizational commitment on employee performance at the Kendari City Revenue Service.